Intervensi Latihan Keterampilan Sosial pada Pasien Perilaku Kekerasan - AS, A. Nur Anna (Journal of Health Education and Literacy, 2019)
Background: Aggressive behavior is the biggest problem that often occurs in inpatient care at psychiatric services so it needs to be a top priority, the frequency of aggression has a negative impact on staff and other patients needs to be taken into consideration. Method: descriptive which conducts research on case study methods by conducting interviews and observations. Results: Social skills training given to clients who want to improve skills in social relations or who are unable to make social relations and creativity that are difficult in relation to others by using the principles of social learning. This social skills training consists of six sessions, where each session takes 45 minutes. Conclusions: Exercise skills can overcome problem solving problems. Recommendations: apply social skills training with intervention in patients aggressive behavior